Faba Greens, Globe Artichoke’s Offshoots, Crenate Broomrape and Summer Squash Greens: Unconventional Vegetables of Puglia (Southern Italy) With Good Quality Traits - Renna, Massimiliano; Signore, Angelo; Paradiso, Vito M.; Santamaria, Pietro (Frontiers in Plant Science, 2018)
Globe artichoke (Cynara cardunculus L. subsp. [L.] scolymus Hayek), summer squash (Cucurbita pepo L.) and faba bean (Vicia faba L.) are widely cultivated for their immature inflorescences, fruits and seeds, respectively. Nevertheless, in some areas of Puglia (Southern Italy), other organs of these species are traditionally used as vegetables, instead of being considered as by-products. Offshoots (so-called cardoni or carducci) of globe artichoke, produced during the vegetative growing cycle and removed by common cultural procedures, are used like to the cultivated cardoons (C. cardunculus L. var. altilis DC). The stems, petioles, flowers and smaller leaves of summer squash are used as greens (so-called cime di zucchini), like other leafy vegetables such as chicory (Cichorium intybus L.) and Swiss chard (Beta vulgaris L.). Also the plant apex of faba bean, about 5-10 cm long, obtained from the green pruning, are used as greens (so-called cime di fava) like spinach leaves. Moreover, crenate broomrape (Orobanche crenata Forssk.), a root parasite plant that produces devastating effects on many crops (mostly legumes), is used like asparagus (Asparagus officinalis L.) to prepare several traditional dishes. In this study ethnobotanical surveys and quality assessment of these unconventional vegetables were performed. For their content of fiber, offshoots of globe artichokes can be considered a useful food to bowel. Summer squash greens could be recommended as a vegetable to use especially in the case of hypoglycemic diets considering both content and composition of their carbohydrates. For their low content of nitrate, faba greens could be recommended as a substitute of nitrate-rich leafy vegetables. Crenate broomrape shows a high antioxidant activity and may be considered as a very nutritious agri-food product. Overall, the results of the present study indicate that offshoots of globe artichoke, summer squash greens, faba greens and crenate broomrape have good potential as novel foods, being nutritious and refined products. Their exploitation aiming to the obtainment of labelled and/or new potential ready-to-eat retail products could satisfy the demand for local functional foods.